2018
DOI: 10.1038/s41598-018-25025-3
|View full text |Cite
|
Sign up to set email alerts
|

Spillover modes in multiplex games: double-edged effects on cooperation and their coevolution

Abstract: In recent years, there has been growing interest in studying games on multiplex networks that account for interactions across linked social contexts. However, little is known about how potential cross-context interference, or spillover, of individual behavioural strategy impact overall cooperation. We consider three plausible spillover modes, quantifying and comparing their effects on the evolution of cooperation. In our model, social interactions take place on two network layers: repeated interactions with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…While the bulk of research concerning evolutionary games on networks has been devoted to single and isolated networks, such as small-world [20][21][22][23][24][25][26], scale-free [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], coevolving [42][43][44][45][46][47][48][49][50], hierarchical [51,52] and community [53] networks, the focus has in recent years been shifting towards multilayer and interdependent networks [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. This research has revealed interdependent network reciproci...…”
Section: Introductionmentioning
confidence: 99%
“…While the bulk of research concerning evolutionary games on networks has been devoted to single and isolated networks, such as small-world [20][21][22][23][24][25][26], scale-free [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], coevolving [42][43][44][45][46][47][48][49][50], hierarchical [51,52] and community [53] networks, the focus has in recent years been shifting towards multilayer and interdependent networks [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. This research has revealed interdependent network reciproci...…”
Section: Introductionmentioning
confidence: 99%
“…In this work we will not assume any sophisticated environmental feedback mechanism [28][29][30] or demanding cognitive skill about players [31][32][33][34][35][36], but only explore the plain consequence of perception error collectively made by group members. To reveal the interaction between strategies and individual skills we consider a coevolutionary model [37][38][39][40][41] where players may not only imitate a more successful strategy but also adopt the way to consider individual achievement when making decisions. In particular, besides individuals who are performing unbiased estimation of their payoff values we also assume the initial presence of over-and underconfident players and monitor the coevolutionary process.…”
Section: Introductionmentioning
confidence: 99%
“…Today, evolutionary games are the workhorse for studying frequency dependent selection in biological systems, and they are used prolifically to investigate cooperation and competition in economic, social, and technological systems [3,4]. In general, evolutionary games allow modelers to make the interactions within a system measurable and interpretable, which pairs particularly well with network science [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%